Patagonian prehistory : human ecology and cultural evolution in the land of giants - Garvey, Raven (The University of Utah Press, 2021)
"Garvey uses human ecology and cultural evolution models to address the reasons for continued hunting and gathering in Patagonia over agriculture"--